2021
DOI: 10.1002/ece3.7516
|View full text |Cite
|
Sign up to set email alerts
|

Grass bud responses to fire in a semiarid savanna system

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 53 publications
2
22
1
Order By: Relevance
“…The reason for this may be related to the mesquite microenvironment re-establishing quickly following top-kill (Ansley et al 2019) and providing a nitrogen boost to Texas wintergrass in the first few years following fire. A recent study found that growing buds in caespitose Texas wintergrass are positioned lower than those of stoloniferous short-grass curly mesquite (Hilaria belangeri) and this may explain the tolerance of this species to even the most intense fires (Hiers et al 2021). We thus reject our hypothesis that the maintenance fires would restore or strengthen trends in herbaceous community responses that were established by the transition fire treatments.…”
Section: Grass Responses To Maintenance Firescontrasting
confidence: 64%
See 1 more Smart Citation
“…The reason for this may be related to the mesquite microenvironment re-establishing quickly following top-kill (Ansley et al 2019) and providing a nitrogen boost to Texas wintergrass in the first few years following fire. A recent study found that growing buds in caespitose Texas wintergrass are positioned lower than those of stoloniferous short-grass curly mesquite (Hilaria belangeri) and this may explain the tolerance of this species to even the most intense fires (Hiers et al 2021). We thus reject our hypothesis that the maintenance fires would restore or strengthen trends in herbaceous community responses that were established by the transition fire treatments.…”
Section: Grass Responses To Maintenance Firescontrasting
confidence: 64%
“…Thus, the rationale for our study was to accelerate the return of fire to the ecosystem via a pyric transition regime (a series of intense, repeated headfires, including some in summer, within a few years) that would top-kill most and possibly root-kill some mesquite compared with single fires, and facilitate the transition to C 4 grassland. This plan assumed the presence of C 4 mid-grass species in the seed and bud bank (Russell et al 2015, Hiers et al 2021 and recognized that C 4 grass recovery might be slower after summer fire (Trollope 1987, Engle et al 2000, Briske et al 2003.…”
Section: Prescribed Transition Firesmentioning
confidence: 99%
“…Bud banks in many fire-prone species are dormant until fire activates them (Ott et al, 2019), and greater severity within the range of our study appears to increase the proportion of buds activated. However, subsequent growth from activated buds is supported by available plant resources (Hiers et al, 2021;Ott et al, 2019), and carbohydrate reserves are likely to be lowest in autumn for L. trinervium, at the end of the active growth season. This suggests that sufficient resources were available for vegetative recovery after either burn season, but as bud activation increased after autumn burns (with fire severity), resources were too limiting for flowering.…”
Section: Resprout Growthmentioning
confidence: 99%
“…2013; Pausas & Paula 2020; Hiers et al . 2021). Temperatures in the soil surface and 50 cm aboveground were extremely elevated, especially in FI‐4 plots, hence even basal and aerial buds could be damaged.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, resprouting, which is the main postfire regeneration strategy in Cerrado open savannas (Pilon et al 2021;Zupo et al 2021), occurs mainly from underground buds (Zupo et al 2021) that are highly protected from fire (Pausas et al 2018). For most species, the vertical distribution of buds in the soil is unknown, but recent studies have shown that even though buds located in the upper layers may get killed, deeper buds are likely to survive and bear new shoots/tillers (Charles-Dominique et al 2015;Hiers et al 2021). However, resprouting can also occur from basal and aerial buds (Moore et al 2019;Zupo et al 2021), which are more likely to be damaged by fires or produce less vigorous resprouts (Clarke et al 2013;Pausas & Paula 2020;Hiers et al 2021).…”
Section: Post-fire Regenerationmentioning
confidence: 99%